Case Report of an Awake Craniotomy in a Patient With Eisenmenger Syndrome. Issue 9 (1st May 2018) - Heifets, Boris D.; Crawford, Erin; Jackson, Ethan; Brodt, Jessica; Jaffe, Richard A.; Burbridge, Mark A.
Abstract : We present a detailed report of an awake craniotomy for recurrent third ventricular colloid cyst in a patient with severe pulmonary arterial hypertension in the setting of Eisenmenger syndrome, performed 6 weeks after we managed the same patient for a more conservative procedure. This patient has a high risk of perioperative mortality and may be particularly susceptible to perioperative hemodynamic changes or fluid shifts. The risks of general anesthesia induction and emergence must be balanced against the risks inherent in an awake craniotomy on a per case basis.